Improving learning in later life [ - Withnall, A. (London ;New York : Routledge, 2010)
Focuses on understanding the varied learning experiences of older people across the life course, analyzing the role and significance of learning in older people's lives. This book links research
1. Lifelong learning : a new climate for older learners? -- 2. Why learning in later life? -- 3. What has influenced later life learners? -- 4. How does later life learning happen? -- 5. No limits to learning? -- 6. New contexts, new learners? -- 7. A better future for older learners?
Description based on print version record
Includes bibliographical references (p 139-147) and index
Keywords: Continuing education; Older people -- Education; Older people